Nanotechnology in functional foods - Bhattacharya, Tanima; Ahmed, Shakeel 1989- (Scrivener Publishing, 2022)
NANOTECHNOLOGY IN FUNCTIONAL FOODSThe broad applicability of bioactive delivery systems for improving food quality, safety, and human health will make this book a valuable resource for a wide range of readers in industry, research, and academia.Functional foods is an emerging trend in the food industry, whose potential value is determined by whether they are safe with respect to consumer health. Nanotechnology in Functional Foods was written to help the reader better understand the benefits and concerns associated with these foods. In addition to giving an overview of the current state-of-the-art in functional foods, different aspects of the advanced research being conducted on their extraction, synthesis, analysis, and biological effects are presented.-
She has published several scientific research articles in international peer-reviewed journals, and her research interests include the fabrication of biocompatible nanostructures and studying their properties and applications in the area of food science, technology, and biomedical sciences.Shakeel Ahmed, PhD, is an assistant professor of Chemistry at the Higher Education Department, Government of Jammu and Kashmir, India. His PhD degree in Chemistry is from Jamia Millia Islamia, A Central University, New Delhi. He has published several research publications in the area of green nanomaterials and biopolymers for various applications including biomedical, packaging, and water treatment. He has published more than 20 books in the area of nanomaterials and green materials.
Keywords: Technische Innovation; Functional Food; Nanotechnologie; Lebensmittelproduktion; Anorganische Chemie; Biochemie; Lebensmitteltechnologie und Getränketechnologie; Biotechnologie; Materialwissenschaft: Biomaterialien, Nanomaterialien, Kohlenstoff; Sonstiges; Bioanorganische Chemie; Bioinorganic Chemistry; Chemie; Chemistry; Food Biotechnology; Food Science & Technology; Lebensmittel; Lebensmittel / Biotechnologie; Lebensmittelforschung u. -technologie; Nanomaterialien; Nanomaterials; Nanotechnology